Experimental study of engine performance and emissions for hydrogen diesel dual fuel engine with exhaust gas recirculation. (3rd May 2019) - Nag, Sarthak; Sharma, Priybrat; Gupta, Arpan; Dhar, Atul
Abstract: With an alarming enlargement in vehicular density, there is a threat to the environment due to toxic emissions and depleting fossil fuel reserves across the globe. This has led to the perpetual exploration of clean energy resources to establish sustainable transportation. Researchers are continuously looking for the fuels with clean emission without compromising much on vehicular performance characteristics which has already been set by efficient diesel engines. Hydrogen seems to be a promising alternative fuel for its clean combustion, recyclability and enhanced engine performance. However, problems like high NOx emissions is seen as an exclusive threat to hydrogen fuelled engines. Exhaust gas recirculation (EGR), on the other hand, is known to overcome the aforementioned problem. Therefore, this study is conducted to study the combined effect of hydrogen addition and EGR on the dual fuelled compression ignition engine on a single cylinder diesel engine modified to incorporate manifold hydrogen injection and controlled EGR. The experiments are conducted for 25%, 50%, 75% and 100% loads with the hydrogen energy share (HES) of 0%, 10% and 30%. The EGR rate is controlled between 0%, 5% and 10%. With no substantial decrement in engine's brake thermal efficiency, high gains in terms of emissions are observed due to synergy between hydrogen addition and EGR. The cumulative reduction of 38.4%, 27.4%, 33.4%, 32.3% and 20% with 30% HES and 10% EGR is observed for NOx, CO2, CO, THC and PM, respectively. Hence, the combination of hydrogen addition and EGR is observed to be advantageous for overall emission reduction. Graphical abstract: Image 1 Highlights: Hydrogen-diesel dual fuel combustion engine with EGR. Synergy between hydrogen and EGR for emission reduction. Detailed engine performance and emission study. EGR with Hydrogen addition is effective in reducing NOx emissions as well as other regulated emissions.